Skin-lightening practices among female high school students in Ghana. (February 2018) - Osei, M.; Ali, M.; Owusu, A.; Baiden, F.
Abstract: Objective: The practice of skin lightening (SL) persist despite warnings about its harmful health effects. Adolescents are particularly vulnerable and at risk of prolonged use of SL products. We explored SL practices among high school students in Ghana, West Africa. Study design: Cross-sectional survey. Methods: We used a self-administered questionnaire in a survey on SL practices among randomly selected female students in five Senior High Schools in the Brong Ahafo Region of Ghana. We determined prevalence and used bivariate and multivariate analysis to identify factors associated with the practice. Results: A total of 410 students with a mean age of 17.6 years (±1.6) participated in the study. While 71.5% of students indicated that they had been approached by relatives and friends to use SL creams, 65.6% admitted to actually using it. Most (85.5%) students identified at least five friends who were using SL products at the time of the survey. Between 22.0% and 44.0% of students knew female teachers who practiced SL. Students in first year were twice as likely to practice SL compared with students in third year (odds ratio [OR] = 1.90, 95% confidence interval [CI] 1.15–3.13). Compared with those who had never been approached, students who had been approached by relatives and friends to use SL products were likely to be using it (OR = 2.24, 95% CI 1.43–3.53). Students who had sisters who used SL products were twice as likely to be users themselves (OR = 1.82, 95% CI 1.12–2.95). Conclusion: The practice of SL among female students in this study is high, and about the same as reported among adults in Ghana and other parts of sub-Saharan Africa. This suggests that the practice is well entrenched. A ban on the sale of SL products to adolescents in Ghana should be considered. Highlights: Over 60% of female high school students engaged in skin lightening. Between 22% and 44% of students know female teachers who practice skin lightening. Female siblings are the greatest identified source of influence. Banned skin-lightening products are in open market and accessible to adolescents.